2017
DOI: 10.1002/anie.201701984
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Recognition of Active Oxygen Species on the Surface of Oxygen Evolution Reaction Electrocatalysts

Abstract: Owing to the transient nature of the intermediates formed during the oxygen evolution reaction (OER) on the surface of transition metal oxides, their nature remains largely elusive by the means of simple techniques. The use of chemical probes is proposed, which, owing to their specific affinities towards different oxygen species, unravel the role played by these species on the OER mechanism. For that, tetraalkylammonium (TAA) cations, previously known for their surfactant properties, are introduced, which inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
116
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(147 citation statements)
references
References 29 publications
14
116
0
1
Order By: Relevance
“…[2][3][4] With the merits of cleanliness and reproducibility, hydrogen energy has been proposed as a promising alternative to fossil fuels. [5][6][7] Currently, electrocatalytic water splitting is considered as a facile and efficient way to produce hydrogen. [8] However, the slow kinetics of two half reactions (HER and OER) restrict the efficiency of overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] With the merits of cleanliness and reproducibility, hydrogen energy has been proposed as a promising alternative to fossil fuels. [5][6][7] Currently, electrocatalytic water splitting is considered as a facile and efficient way to produce hydrogen. [8] However, the slow kinetics of two half reactions (HER and OER) restrict the efficiency of overall water splitting.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27] Generally,these results show that the catalytic performance and active-phase structure of NiOOH catalysts can be tuned by changing the electrolyte cation and Fe contents in the electrolyte. [13][14][15]23] Grimaud et al [28] also studied the interaction of cations with the NiOOH structure.T hey showed that tetraalkylammonium cations (TTA + )interact with the oxygen species formed upon deprotonation and these interactions only occur for Fecontaining NiOOH catalysts.…”
mentioning
confidence: 99%
“…TheT afel slopes also increase from 66 mV dec À1 in protic solution to 81 mV dec À1 in deuterated solution (Figure 3b), which indicates there is ad ifference in the Gibbs free energy of the intermediate that affects the reaction rate. [14] TheK IE values are associated with the current density ratios in the H 2 Oand D 2 Osolutions according to:K IE = k H /k D = j 0 H C 0 D /j 0 D C 0 H (detailed information can be found in the experimental section of the Supporting Information). [15] In the current study,t he k H /k D value is 2.40 at 1.60 V, which suggests as ignificant primary isotope effect arising from aw ater oxidation reaction.…”
mentioning
confidence: 99%